Detection of Human Papillomavirus DNA in Cutaneous Squamous Cell Carcinoma among Immunocompetent Individuals - Asgari, Maryam M. (2008)
The presence of certain types of human papillomavirus (HPV) is a known risk factor for the development of anogenital squamous cell carcinomas (SCCs). A similar association has been hypothesized for cutaneous SCCs, although, to our knowledge, no studies to date have combined sensitive HPV DNA detection techniques with epidemiologic data controlling for known risk factors to explore the association. We designed a case–control study examining HPV prevalence using highly sensitive PCR-detection assays in tissue samples from 85 immunocompetent patients with histologically confirmed SCCs and 95 age-matched individuals without a prior history of skin cancer. A standardized interview was administered to all study subjects to collect information pertaining to potential confounding variables. The overall detection rate of HPV DNA was high in case lesions (54%) and perilesions (50%) and in both sun-exposed normal tissue (59%) and non-sun-exposed normal tissue (49%) from controls. In comparing case tissue to control tissue, there was no differential detection of HPV DNA across various HPV species. However, HPV DNA from β-papillomavirus species 2 was more likely to be identified in tumors than in adjacent healthy tissue among cases (paired analysis, odds ratio = 4.0, confidence interval = 1.3–12.0). The high prevalence of HPV DNA detected among controls suggests that HPV DNA is widely distributed among the general population. However, the differential detection of HPV β-papillomavirus species in tumors among cases suggests that certain HPV types may be involved in the progression of cutaneous SCCs.